NHC-catalyzed enantioselective synthesis of β-trifluoromethyl-β-hydroxyamides - Davies, Alyn T.; Greenhalgh, Mark D.; Slawin, Alexandra M. Z.; Smith, Andrew D. (Beilstein Journal of Organic Chemistry, 2020)
The N-heterocyclic carbene (NHC)-catalyzed formal [2 + 2] cycloaddition between α-aroyloxyaldehydes and trifluoroacetophenones, followed by ring opening with an amine or a reducing agent is described. The resulting β-trifluoromethyl-β-hydroxyamide and alcohol products are produced with reasonable diastereocontrol (typically ≈70:30 dr) and excellent enantioselectivity, and they can be isolated in moderate to good yield as a single diastereoisomer.
Keywords: enantioselective catalysis; formal [2 + 2] cycloaddition; N-heterocyclic carbene; ring opening; trifluoromethyl group

(untitled) - Purser, S.; Moore, P. R.; Swallow, S.; Gouverneur, V. (Chem. Soc. Rev., 2008)

(untitled) - Müller, K.; Faeh, C.; Diederich, F. (Science, 2007)

(untitled) - Studer, A. (Angew. Chem., Int. Ed., 2012)

(untitled) - Tomashenko, O. A.; Grushin, V. V. (Chem. Rev., 2011)

(untitled) - Dilman, A. D.; Levin, V. V. (Eur. J. Org. Chem., 2011)

(untitled) - Liu, H.; Gu, Z.; Jiang, X. (Adv. Synth. Catal., 2013)

(untitled) - Hagmann, W. K. (J. Med. Chem., 2008)

(untitled) - Sani, M.; Volonterio, A.; Zanda, M. (ChemMedChem, 2007)

(untitled) - Léger, S.; Bayly, C. I.; Black, W. C.; Desmarais, S.; Falgueyret, J.-P.; Massé, F.; Percival, M. D.; Truchon, J.-F. (Bioorg. Med. Chem. Lett., 2007)

(untitled) - Nie, J.; Guo, H.-C.; Cahard, D.; Ma, J.-A. (Chem. Rev., 2011)

(untitled) - Shibata, N.; Matsnev, A.; Cahard, D. (Beilstein J. Org. Chem., 2010)

(untitled) - Ma, J.-A.; Cahard, D. (Chem. Rev., 2004)

(untitled) - Valero, G.; Companyó, X.; Rios, R. (Chem. – Eur. J., 2011)
See for a review.

(untitled) - Yang, W.; Cui, Y.-M.; Zhou, W.; Li, L.; Yang, K.-F.; Zheng, Z.-J.; Lu, Y.; Xu, L.-W. (Synlett, 2014)

(untitled) - Vlasserou, I.; Sfetsa, M.; Gerokonstantis, D.-T.; Kokotos, C. G.; Moutevelis-Minakakis, P. (Tetrahedron, 2018)

(untitled) - Duangdee, N.; Harnying, W.; Rulli, G.; Neudörfl, J.-M.; Gröger, H.; Berkessel, A. (J. Am. Chem. Soc., 2012)

(untitled) - Hara, N.; Tamura, R.; Funahashi, Y.; Nakamura, S. (Org. Lett., 2011)

(untitled) - Kokotos, C. G. (J. Org. Chem., 2012)

(untitled) - Qui, L.-H.; Shen, Z.-X.; Shi, C.-Q.; Liu, Y.-H.; Zhang, Y.-W. (Chin. J. Chem., 2005)

(untitled) - Thomson, C. J.; Barber, D. M.; Dixon, D. J. (Angew. Chem., Int. Ed., 2020)

(untitled) - Moore, J. L.; Rovis, T. (Top. Curr. Chem., 2010)

(untitled) - Marion, N.; Díez-González, S.; Nolan, S. P. (Angew. Chem., Int. Ed., 2007)

(untitled) - Enders, D.; Niemeier, O.; Henseler, A. (Chem. Rev., 2007)

(untitled) - Hopkinson, M. N.; Richter, C.; Schedler, M.; Glorius, F. (Nature, 2014)

(untitled) - Ryan, S. J.; Candish, L.; Lupton, D. W. (Chem. Soc. Rev., 2013)

(untitled) - Flanigan, D. M.; Romanov-Michailidis, F.; White, N. A.; Rovis, T. (Chem. Rev., 2015)

(untitled) - Vora, H. U.; Wheeler, P.; Rovis, T. (Adv. Synth. Catal., 2012)

(untitled) - Douglas, J.; Churchill, G.; Smith, A. D. (Synthesis, 2012)

(untitled) - Zhang, Y.-R.; He, L.; Wu, X.; Shao, P.-L.; Ye, S. (Org. Lett., 2008)

(untitled) - Duguet, N.; Campbell, C. D.; Slawin, A. M. Z.; Smith, A. D. (Org. Biomol. Chem., 2008)

(untitled) - He, M.; Uc, G. J.; Bode, J. W. (J. Am. Chem. Soc., 2006)

(untitled) - He, M.; Beahm, B. J.; Bode, J. W. (Org. Lett., 2008)

(untitled) - Kobayashi, S.; Kinoshita, T.; Uehara, H.; Sudo, T.; Ryu, I. (Org. Lett., 2009)

(untitled) - Yang, L.; Wang, F.; Chua, P. J.; Lv, Y.; Zhong, L.-J.; Zhong, G. (Org. Lett., 2012)

(untitled) - Jian, T.-Y.; Sun, L.-H.; Ye, S. (Chem. Commun., 2012)

(untitled) - Lv, H.; Chen, X.-Y.; Sun, L.-h.; Ye, S. (J. Org. Chem., 2010)

(untitled) - Jian, T.-Y.; Shao, P.-L.; Ye, S. (Chem. Commun., 2011)

(untitled) - Chen, X.; Fang, X.; Chi, Y. R. (Chem. Sci., 2013)

(untitled) - Hao, L.; Du, Y.; Lv, H.; Chen, X.; Jiang, H.; Shao, Y.; Chi, Y. R. (Org. Lett., 2012)

(untitled) - Lee, A.; Younai, A.; Price, C. K.; Izquierdo, J.; Mishra, R. K.; Scheidt, K. A. (J. Am. Chem. Soc., 2014)

(untitled) - Cheng, J.-T.; Chen, X.-Y.; Ye, S. (Org. Biomol. Chem., 2015)

(untitled) - Lee, A.; Scheidt, K. A. (Chem. Commun., 2015)

(untitled) - Zhao, X.; Ruhl, K. E.; Rovis, T. (Angew. Chem., Int. Ed., 2012)

(untitled) - Dong, X.; Yang, W.; Hu, W.; Sun, J. (Angew. Chem., Int. Ed., 2015)

(untitled) - Lin, L.; Yang, Y.; Wang, M.; Lai, L.; Guo, Y.; Wang, R. (Chem. Commun., 2015)

(untitled) - Wang, X.-N.; Shao, P.-L.; Lv, H.; Ye, S. (Org. Lett., 2009)

(untitled) - Mo, J.; Yang, R.; Chen, X.; Tiwari, B.; Chi, Y. R. (Org. Lett., 2013)

(untitled) - Ling, K. B.; Smith, A. D. (Chem. Commun., 2011)

(untitled) - Davies, A. T.; Taylor, J. E.; Douglas, J.; Collett, C. J.; Morrill, L. C.; Fallan, C.; Slawin, A. M. Z.; Churchill, G.; Smith, A. D. (J. Org. Chem., 2013)

(untitled) - Taylor, J. E.; Daniels, D. S. B.; Smith, A. D. (Org. Lett., 2013)

(untitled) - Davies, A. T.; Pickett, P. M.; Slawin, A. M. Z.; Smith, A. D. (ACS Catal., 2014)

(untitled) - Attaba, N.; Taylor, J. E.; Slawin, A. M. Z.; Smith, A. D. (J. Org. Chem., 2015)

(untitled) - Kerr, R. W. F.; Greenhalgh, M. D.; Slawin, A. M. Z.; Arnold, P. L.; Smith, A. D. (Tetrahedron: Asymmetry, 2017)

(untitled) - Uyanik, M.; Suzuki, D.; Yasui, T.; Ishihara, K. (Angew. Chem., Int. Ed., 2011)

(untitled) - Davies, A. T.; Slawin, A. M. Z.; Smith, A. D. (Chem. – Eur. J., 2015)

(untitled) - McDaniel, D. H.; Brown, H. C. (J. Org. Chem., 1958)

(untitled) - Massey, R. S.; Collett, C. J.; Lindsay, A. G.; Smith, A. D.; O’Donoghue, A. C. (J. Am. Chem. Soc., 2012)

(untitled) - Collett, C. J.; Massey, R. S.; Maguire, O. R.; Batsanov, A. S.; O' Donoghue, A. C.; Smith, A. D. (Chem. Sci., 2013)

(untitled) - Barrios Antúnez, D.-J.; Greenhalgh, M. D.; Brueckner, A. C.; Walden, D. M.; Elías-Rodríguez, P.; Roberts, P.; Young, B. G.; West, T. H.; Slawin, A. M. Z.; Ha-Yeon Cheong, P.; Smith, A. D. (Chem. Sci., 2019)